The Effect of Music Listening and Progressive Muscle Relaxation on The Stress Level of Novice Music Teachers during Coronavirus Disease 2019 (Covid-19) in Malaysia - Peyee, Yong; Wing, Cheong Ku; Hwa, Poon Chiew (Harmonia: Journal of Arts Research and Education, 2021)
The outbreak of Coronavirus Disease 2019 (COVID-19) has contributed stress to many people around the world due to fear and anxiety. Other than health issues, it has threatened the overall economy and influenced a drastic change of lifestyle. The purpose of this quasi-experimental study was to examine the effect of music listening and progressive muscle relaxation (PMR) on the stress level of novice music teachers in Malaysia by using a mixed-method research design, combining quantitative and qualitative approaches. Based on the pre-test questionnaire, a sample of 30 participants was divided equally into high-moderate stress and low-stress groups based on Perceived Stress Scale-10 (PSS-10). The quantitative results revealed a significant decrease in stress scores among the majority of the novice music teachers from high-moderate stress groups and insignificant differences in low-stress groups. The intervention was found to be effective as a stress-reduction therapy and benefits more on participants with higher stress levels. Ten interviewees were selected from the 30 participants to examine their career-stress-related challenges. The qualitative findings were divided into professional and non-professional challenges, included online teaching and learning, time management, financial issues, physiological issues, and emotional issues.Â Â